Model Petri Net Pengajuan KKN Mahasiswa Universitas Lampung - Hamzah, Nur; Sholehurrohman, Ridho; Sutawa, Wira Adiguna; Hana, Lathifatul (Contemporary Mathematics and Applications (ConMathA), 2024)
The Petri Net (PN) model is a powerful mathematical representation for describing dynamic systems involving processes, states, and interactions between its elements. The use of the Petri Net Model has been applied in various contexts, in this research the Petri Net is used to represent the KKN (Real Work Lecture) application flow for students at the University of Lampung. This modeling provides a clear visual representation of the steps required, the stages that must be passed, and the relationships between elements in the KKN application process. This Petri Net Model analysis helps in identifying potential points that can cause delays or errors in the KKN application process. With a better understanding of inter-entity interactions and process flows, improvements and optimization of KKN application procedures can be implemented. The research results show that the use of the Petri Net Model in the context of KKN applications for Lampung University students has great potential to increase efficiency, reduce errors, and speed up the application process.